Controlled Continuous ∗-K-g-Frames for Hilbert C∗-Modules - Abdeslam Touri; Hatim Labrigui; Mohamed Rossafi; Samir Kabbaj (Abstract and Applied Analysis)
Frame theory has a great revolution for recent years. This theory has been extended from Hilbert spaces to Hilbert C∗-modules. In this paper, we define and study the new concept of controlled continuous ∗-K-g-frames for Hilbert C∗-modules and we establish some properties.